PROFIL PENGOBATAN OBAT ISPA NON PNEUMONIA PADA ANAK DI PUSKESMAS MANTANG LOMBOK TENGAH - Dwi Monika Ningrum (Politeknik Medica Farma Husada Mataram, 2022)
Acute Respiratory Infection (ARI) is an acute infection that attacks the organs of the upper respiratory tract and lower respiratory tract. Acute respiratory infection is a disease that mostly affects children and adults in developing and developed countries. Non-pneumonic acute respiratory tract infections include a group of patients with under-fives with a cough that does not show symptoms of an increase in respiratory rate and does not show any pull from the lower chest wall. This study aims to see the description of ARI non-pneumonia treatment at the Mantang Health Center, Central Lombok. Sampling in this study used all patients who met the inclusion criteria, and data obtained were 21 patients with a diagnosis of ARI Non Pneumonia in children from 665 patient populations. The results obtained in this study were obtained the most patients, namely patients aged 4-6 years with a percentage of 42.85%, ages 1-3 years 7 with a percentage of 33.33%, age < 6 months of 14.28% and 6-12 months with a percentage of 14.28%. The classes of drugs prescribed for the May 2021 period are antibiotics, antihistamines, analgesics, mucolytics, anti-inflammatory, and multivitamins . The conclusion obtained in this study is that pediatric patients with ARI Non-Pneumonia at the Mantang Health Center who received the most treatment at the age of 4-6 years had the highest percentage and received the most therapy with a diagnosis of ARI Non-Pneumonia, which was given antihistamins